Observing simulated galaxy clusters: The prospects of ICM velocity diagnostics. Issue 4 (2nd May 2013) - Biffi, V.; Dolag, K.; Böhringer, H.; Schartel, Norbert
Abstract Non‐thermal motions in the intra‐cluster medium (ICM) are believed to play a non‐negligible role in the pressure support to the total gravitating mass of galaxy clusters. Future high‐precision X‐ray missions will allow us to directly detect the signature of these motions from highly resolved spectra of the ICM. With this perspective, we will present here a study on a set of clusters extracted from a cosmological hydrodynamical simulation, for which we simulated X‐ray observations and characterized them via the non‐thermal velocity amplitude of the ICM. We have applied the X‐ray virtual telescope PHOX to generate mock observations of the simulated clusters and estimated in an observational fashion global X‐ray properties. We included ICM non‐thermal motions as additional parameter to further identify non‐regular clusters. In particular, the influence of internal gas motions on the location of clusters in the LX‐T plane was investigated and was found that objects with the largest amount of non‐thermal velocity have on average higher X‐ray luminosities. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)